Implementation of gaming In the cloud through construct engine applications on heroku infrastructure - Khaerul Imam Phatoni; Rochedi Idul Adha; Jonson Manurung; M Azhar Prabukusumo; Rizqullah Aryaputra Piliang; Muhammad Sulthan Nasyira (Institute of Computer Science (IOCS), 2026)
This study presents a performance analysis of real-time multiplayer gaming through web-based game engines deployed on cloud Platform-as-a-Service infrastructure, specifically examining Construct 3 integration with Heroku's managed deployment platform. A multiplayer Pong game was developed to evaluate the viability of browser-based gaming architectures for real-time applications, utilizing WebSocket communication protocols, room-based session management, and hybrid client-server prediction models. The implementation demonstrates five architectural components: secure WebSocket connection establishment, 60 frames-per-second server-side game state synchronization, minimal cloud deployment configuration, scalable room management supporting multiple concurrent sessions, and responsive input handling with client-side prediction. Performance evaluation with ten concurrent game instances revealed exceptional resource efficiency, consuming maximum 34 megabytes memory with dyno load averages of 0.01, validating JavaScript-based server implementations for real-time gaming applications. The results indicate that web-based game engines can achieve performance characteristics traditionally associated with dedicated server architectures while maintaining significant advantages in development velocity, deployment simplicity, and operational efficiency. The study contributes evidence supporting the democratization of multiplayer game development through accessible web technologies, demonstrating that traditional barriers between browser-based and native gaming applications are diminishing as platform capabilities mature. These findings establish benchmarks for web-based multiplayer gaming performance and provide foundation for future research in cloud-based game development paradigms.